2022
DOI: 10.3390/en15051859
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Nexus among Energy Consumption, Environmental Degradation, Financial Development and Health Outcome: Empirical Study for Pakistan

Abstract: Pakistan is facing an energy crisis and is also severely affected by climate change. Moreover, Pakistan is not doing well as far as health outcome indicators are concerned. The causal nexus among energy, environment, and health outcomes is well-established in literature. Besides, financial development also grabs the attention of health outcome literature as financial development can play a significant role in improving health outcomes. Thus, this study was conducted to test the causal nexus among energy consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The findings show that CO 2 emissions affect inversely health outcomes. More recently, the study of Arafat et al ( 30 ) analyzed the causality relationship between CO 2 emissions, life expectancy, and IMR in the case of Pakistan by applying causality cointegration and causality methods. The causality analysis findings showed the occurrence of a unidirectional link moving from CO 2 emissions to life expectancy and IMR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings show that CO 2 emissions affect inversely health outcomes. More recently, the study of Arafat et al ( 30 ) analyzed the causality relationship between CO 2 emissions, life expectancy, and IMR in the case of Pakistan by applying causality cointegration and causality methods. The causality analysis findings showed the occurrence of a unidirectional link moving from CO 2 emissions to life expectancy and IMR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study recorded a causal relationship between environmental quality, education, and health. Arafat et al (2022) examined the causal nexus between energy consumption, environmental degradation, nancial development, and health outcomes for Pakistan. They recorded a unidirectional causality from energy consumption and environmental degradation to health outcomes, while bidirectional causality was discovered between nancial development and health outcomes in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 1 provides a summary of these studies. The literature in Table 1 might be classified as follows: i) There is a consensus in the literature that environmental degradation rises infant mortality (Ecevit & Çetin, 2016;Majeed & Khan, 2019;Erdoğan et al, 2019;Shobande, 2020;Majeed & Ozturk, 2020;Omri et al, 2022;Yu et al, 2022;Tsai et al, 2022;Barua et al, 2022) and reduces life expectancy (Balan, 2016;Sirag et al, 2017;Matthew et al, 2018;Nkalu & Edeme, 2019;Erdoğan et al, 2019;Majeed & Khan, 2019;Majeed & Ozturk, 2020;Akter et al, 2020;Hossain et al, 2020;Rodriguez-Alvarez, 2021;Murthy et al, 2021;Alimi & Ajide, 2021;Chen et al, 2021;Bouchoucha, 2021;Rjoub et al, 2021;Azam et al, 2022;Omri et al, 2022;Rahman & Alam, 2022a;Arafat et al, 2022;Radmehr & Adebayo, 2022;Salehnia et al, 2022;Ibrahim, 2022;Bayar et al, 2022). Also, Mutizwa and Makochekanwa (2015) concluded that environmental degradation does not have an impact on infant mortality.…”
Section: Literaturementioning
confidence: 99%